Review of photovoltaic and wind power systems utilized in the mining industry. (August 2017) - Choi, Yosoon; Song, Jinyoung
Abstract: This paper reports recent efforts made by the mining industry in adapting and applying photovoltaic (PV) and wind power systems at operating and abandoned mines around the world. Several applications of PV systems have been found at operating mines such as the Goldstrike mine in USA, Chuquicamata mine in Chile, Weipa and DeGrussa mines in Australia, Thaba mine in South Africa, and the Rosebel mine in Suriname. A few PV systems were also identified at abandoned mines in USA, Germany, Canada, and Korea. Applications of wind power systems in operating mines were investigated, including those at the Veladero mine in Argentina, Diavik and Raglan mines in Canada; and the Los Pelambres mine in Chile. In addition, some large-scale wind farms constructed at abandoned mines in the USA (i.e., Dave Johnston, Somerset, and Buffalo Mountain) were studied. From the review, we learned that PV and wind power systems have been utilized at mines operating in remote areas to resolve energy supply problems, and at abandoned mines to foster substitute industries able to benefit from exhausted mines. Because the utilization of PV and wind power systems by the mining industry will have positive effects in both environmental and economic terms, it is expected to continue to spread.